Direct Determination of Glycidyl Esters of Fatty Acids in Vegetable Oils by LC–MS - Blumhorst, Michael R. (Springer-Verlag, 2011)
An LC–MS method using a single quadrupole mass spectrometer was developed for direct analysis of glycidyl esters of fatty acids in vegetable oils. Without any sample clean-up, this method provided acceptable recovery of seven glycidyl esters, comparable results to a previously-published method utilizing two solid-phase extraction steps, and consistent detection parameters after greater than 200 injections without any cleaning operations performed. This method could readily be implemented as a screening assay for glycidyl esters in most oil laboratories.